Clinical and epidemiological characteristics of measles in children in the Astrakhan region - O. G. Kimirilova; G. A. Kharchenko (Лечащий Врач)
Analysis of epidemiological data and clinical symptoms of 293 cases of measles in children under 17 years old, confirmed by immuno-enzyme analysis was performed. It was identified that the incidence of measles in Astrakhan region is characterized by the involvement in the epidemic process of children aged less than 1 year and aged 1 to 2 years, not vaccinated against measles, the infection of which occurred as a result of nosocomial outbreaks of the disease. Children of other age groups were more often infected as a result of measles being brought into organized children’s groups. The causes of measles vaccinated children can be: violations of immunization rules, unreliability of official data on vaccination against measles. It is possible to consider the need for additional revaccination against measles at the age of 16 years, which can contribute to the elimination of measles.